2020
DOI: 10.1186/s12889-020-08480-4
|View full text |Cite|
|
Sign up to set email alerts
|

Inequalities in the utilisation of maternal health Care in Rural India: Evidences from National Family Health Survey III & IV

Abstract: Background: Since the implementation of National Rural Health Mission (NRHM) in 2005, Maternal Mortality Ratio has significantly declined in India through a noticeable improvement in maternal health care services. However, India did not succeed to achieve the target of millennium development goal to reduced maternal mortality ratio by 2015. Also, there is substantial inequality exist at the regional, geographic, economic, and social level, and various socioeconomic factors contribute to the significantly large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 40 publications
16
57
1
Order By: Relevance
“…In our study, young women with no exposure to any kind of mass media were found to be less likely to use full ANC and SBA. This result concurs with the ndings from various other studies in which exposure to mass media had a positive association with the utilization of maternity care services [47,61,71,72]. Mass media is an important source of information on health and existing health care programs or policies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, young women with no exposure to any kind of mass media were found to be less likely to use full ANC and SBA. This result concurs with the ndings from various other studies in which exposure to mass media had a positive association with the utilization of maternity care services [47,61,71,72]. Mass media is an important source of information on health and existing health care programs or policies.…”
Section: Discussionsupporting
confidence: 90%
“…Concerning birth order, the likelihood of using full ANC and SBA decreases signi cantly with the increase in birth order. Several other studies have reported similar nding [38,40,47,69]. Primiparous women may have fear of rst pregnancy and are more afraid of complications and di culties during delivery.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…As in the literature on determinants of antenatal care use in developing countries , research in Egypt has confirmed the importance of both social and health needs as determinants of antenatal care [14,18,19,25,27]. On the social side, women's age or age at birth, their education, their husbands' education level, the women's work status, the household standard of living/wealth, and place of residence, assessed in terms of regional level or by rural/urban differentiation, were identified as significant determinants of antenatal care [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][31][32][33][34]. On the health dimension, most research highlighted the significant contribution of parity/birth order, previous birth experience, attributes of current pregnancy (in particular preceding birth interval), the survival status of the previous birth, and the experience of a terminated pregnancy [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Determinants and Inequality Of Antenatal Care In Egyptmentioning
confidence: 99%
“…Other research efforts focused on monitoring changes in the use of antenatal care over time [27,29]. Modeling any use of antenatal care separately for the years 2000 and 2014, Zaky and colleagues showed that wealth, higher education attainment of both women and their husbands, and residence in frontier governorates were significantly related to the use of any antenatal care in 2000 [29]. However, most of these determinants had lost their significance, in particular education and regional differences, by 2014.…”
Section: Determinants and Inequality Of Antenatal Care In Egyptmentioning
confidence: 99%